If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7 = 79 + -2x Reorder the terms: -7 + 6x = 79 + -2x Solving -7 + 6x = 79 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -7 + 6x + 2x = 79 + -2x + 2x Combine like terms: 6x + 2x = 8x -7 + 8x = 79 + -2x + 2x Combine like terms: -2x + 2x = 0 -7 + 8x = 79 + 0 -7 + 8x = 79 Add '7' to each side of the equation. -7 + 7 + 8x = 79 + 7 Combine like terms: -7 + 7 = 0 0 + 8x = 79 + 7 8x = 79 + 7 Combine like terms: 79 + 7 = 86 8x = 86 Divide each side by '8'. x = 10.75 Simplifying x = 10.75
| 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= | | 4/3p=16 | | h(t)=5t^2-30t+45 | | 3/2n=15 | | 2(-3)+16-(3+4)= | | B=900(1+.02) | | d/5+4=9 | | 24-6x=24 | | 20(t)=5t^2-30t+45 | | 5(X+3)-3X=55 | | -5(t-5)+7=6t-3 | | 3x+97=7x+37 |